Occupational Stress and Mental Health Among Healthcare Workers Serving Socially Vulnerable Populations During the COVID-19 Pandemic - Salgado de Snyder, V. Nelly; Villatoro, Alice P.; McDaniel, Marisol D.; Ocegueda, Ana Sofia; Garcia, Deliana; Parra-Medina, Deborah (Frontiers in Public Health, 2021)
The purpose of this study was to analyze occupational and personal stressors, mental health indicators, perceived discrimination and help-seeking behaviors among healthcare workers and providers (HCWPs) serving socially vulnerable groups such as immigrants, refugees, farmworkers, homeless individuals, people living in poverty, and other disadvantaged populations in the United States (U.S.) during the COVID-19 pandemic. Using a cross-sectional descriptive approach, we gathered information between July and September 2020, from a sample of 407 affiliates of two national organizations of clinic-based HCWPs who worked at federally funded and community safety-net clinics. Informed consent was obtained from all participants who completed a self-administered online survey available in English and Spanish. Our results indicated that the HCWPs serving vulnerable groups in the midst of the pandemic experienced high levels of occupational and personal stressors as well as anxiety and depressive symptomology. Major occupational stressors were excessive workload, long working-hours, and institutional barriers to refer and follow-up on their clients' access to needed social services. High-rated personal stressors included sleep disorders, lack of and child-care, partner's loosing job, and other family related situations. Our findings suggest that HCWPs working with vulnerable populations need specialized interventions that bolster their mental health and well-being as the pandemic continues to unfold. We recommend implementing initiatives that encourage HCWPs' to be actively involved in clinic decisions regarding employee safety and protection as well as in management decisions to improve work place infrastructure and capacity to respond to the social needs of their clients. Lessons learned from the pandemic are useful tools in designing protocols for addressing the mental-health needs of HCWPs in health-care organizations that attend to socially underprivileged populations.